Manifestación en Barcelona. El Alcalde en el balcón del Ayuntiamiento. Series of 4 photos. Copied from CNT collection
Manifestación en Barcelona. El Alcalde en el balcón del Ayuntiamiento. Series of 4 photos. Copied from CNT collection.